Characteristics and outcomes of infective endocarditis in South Africa: A retrospective cohort study - Poerstamper, Simon; Pecoraro, Alfonso J.K.; Doubell, Anton F. (SA Heart Journal, 2024)
Background: Infective endocarditis (IE) remains a disease with significant morbidity and mortality for a predominantly young group of patients in South Africa. There is a paucity of data assessing contemporary outcomes of IE in South Africa, limiting our ability to institute strategies to improve the outcome of patients with IE in South Africa. Methods: A retrospective cohort of patients with IE was established from healthcare records for the period of 1 January 2017 - 31 December 2018. A profile of clinical, laboratory, microbiologic, echocardiographic, surgical, and morbidity and mortality data was compiled for each patient. Results: A total of 75 patients with definite IE were included in this study. The mean age was 39.6 years with a male preponderance (68%). Mortality at 6 months (all cause) was 34.7% and embolic complications were common, especially cerebral embolism (21%). Rheumatic heart disease (RHD) was present in 28% of the cohort. A high rate of blood culture negative IE (BCNIE) was present (62.7%). In patients with a positive blood culture, Staphylococcus aureus (43%) and the viridans group of streptococci (32%) were the most common causative organisms. Conclusion: IE in South Africa remains a disease with a significant mortality rate despite the young age of the patients affected. The high rate of BCNIE is a likely contributor to the associated adverse outcomes. Some of the features of IE in South Africa have evolved to resemble a profile of disease similar to cohorts from high-income countries with a Staphylococcal predominance and a reduction in underlying RHD as predisposing risk factor.